RNR STRATEGY 2040: Bhutan-IFPRI collaboration and beyond - Pal, Barun Deb; Gurung, Tayan Raj; Pathak, Himanshu (International Food Policy Research Institute, 2022)
The agriculture sector in Bhutan has evolved progressively from subsistence to integrated semi-commercial sector, and encompasses forestry, agriculture, and livestock, collectively termed as Renewable Natural Resources (RNR). Systematic development since the 1960s has helped improve production of crops, livestock, and overall management of natural resources. Agriculture continues to be a major source of employment after five decades of planned development, with a staggering 51 percent of its population in farming, of which 61.7 percent are female (NSB 2019). Bhutan has also successfully maintained 71 percent of its natural forest cover (FRMD 2018), representing extensive carbon sequestration sink and making the country carbon-negative. Bhutan’s “green” approach to development, founded on the philosophy of Gross National Happiness and more particularly its local values, culture, and religious beliefs of coexistence with nature, has helped in maintaining remarkably stable forest cover and clean environment. Forest cover in Bhutan consists predominantly of broad-leaved trees accounting for 50 percent coverage (1.928 million ha), while 20 percent cover is provided by coniferous trees. The estimated forest biomass of about 973 million tonnes serves as a significant terrestrial carbon sink, amounting to 457 million tonnes of carbon (FRMD 2018). The forests of Bhutan show a wide range of ecological variation and species diversity offering wide variety of social and economic benefits, ranging from easily quantifiable economic values associated with forest products to less tangible services and contributions to society, thereby serving as the foundation of sustainable development. This initiative of collaboration resulted into formalization of a Memorandum of Understanding (MoU) between the Ministry of Agriculture and Forests (MoAF) and IFPRI on July 19, 2019, that defines the areas of cooperation between the two institutions. Since the initiation of this MoU in late 2018, MoAF and IFPRI started working on the collaboration which focused on capacity development of MoAF in policy analysis and visioning. This report aims to provide synopsis of MoAF–IFPRI collaborations from 2018 to 2020, highlighting the main output and defining areas of future collaborations.